2015
DOI: 10.1021/acs.jpcb.5b03565
|View full text |Cite|
|
Sign up to set email alerts
|

Excited State Relaxation of Neutral and Basic 8-Oxoguanine

Abstract: 8-Oxo-7,8-dihydro-2'-deoxyguanosine (8-oxo-dGuo) is one of the most common forms of DNA oxidative damage. Recent studies have shown that 8-oxo-dGuo can repair cyclobutane pyrimidine dimers in double-stranded DNA when photoexcited, making its excited state dynamics of particular interest. The excited state lifetimes of 8-oxo-dGuo and its anion have been previously probed using transient absorption spectroscopy; however, more information is required to understand the decay mechanisms. In this work, excited state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…In sum, our conformation search not only reproduced the neutral, ,, protonated, and deprotonated , 8-oxoG conformers reported in the literature, but identified many new structures. On the basis of their populations calculated at 298 K, [8-oxoG + H] + _1, [8-oxoG + H] + _2·W67, [8-oxoG – H] − _1, [8-oxoG – H] − _1·W67 represent dominant reactants in gas-phase reactions, and were used as starting structures in construction of reaction PESs.…”
Section: Resultssupporting
confidence: 66%
“…In sum, our conformation search not only reproduced the neutral, ,, protonated, and deprotonated , 8-oxoG conformers reported in the literature, but identified many new structures. On the basis of their populations calculated at 298 K, [8-oxoG + H] + _1, [8-oxoG + H] + _2·W67, [8-oxoG – H] − _1, [8-oxoG – H] − _1·W67 represent dominant reactants in gas-phase reactions, and were used as starting structures in construction of reaction PESs.…”
Section: Resultssupporting
confidence: 66%
“…Photophysical and photochemical properties of 2a, 3a and their nucleosides (2b and 3b) have not been documented although their synthetic studies were reported (20)(21)(22)(23). 8-Oxoguanine (with a carbonyl group at 8-position of the purine ring and also known as an oxidation photoproduct of guanine (4a)) was reported to exhibit a redshifted absorption band relative to its 6-oxo-analogs (4a and 4b) (24)(25)(26). In addition to 1a and 1b, thiocarbonyl-modified pyrimidine bases (such as thiolated-uracil and thiolated-thymine) have a strong absorption maximum at longer wavelength than their respective unthiolated nucleobases (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…It is firmly established that the photo-excited state of neutral 8-oxo-G has a sub-picosecond lifetime in aqueous solution, while deprotonated 8-oxo-G − exhibits a much longer fluorescence lifetime of 43 ps [ 26 ]. The drastic shortening of the excited-state lifetime of 8-oxo-G − relative to neutral 8-oxo-G has been explained by either CIs intrinsic to guanine, which are more easily accessible in the neutral than in the anionic form [ 57 ], or by an EDPT reaction along the H-bond between guanine and ribose in 8-oxo-guanosine, which is available in the neutral form, but not in the anionic form [ 23 ]. It has been speculated that the long lifetime of anionic 8-oxo-G − should be favorable for repair by electron transfer in the excited state, while the very short excited-state lifetime of neutral 8-oxo-G should be detrimental in this respect [ 26 ].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Correspondingly, the latter shows a significant quantum yield for fluorescence [ 26 ]. More recent fluorescence up-conversion and theoretical studies led to the conclusion that neutral 8-oxo-G exhibits an ultrafast radiationless decay via two CIs which are accessible by certain out-of-plane deformations of guanine, whilst the longer lifetime of anionic 8-oxo-G − was attributed to the existence of sizable barriers along the reaction paths connecting the Franck-Condon region to the S 1 /S 0 CIs [ 57 ]. This mechanism was also explored by Changenet-Barret et al for the neutral form [ 58 ].…”
Section: Introductionmentioning
confidence: 99%